Predictors of intention to stop substance abuse users after receiving addiction treatment in Phetchabun Province - Roopkhaw, Kampanart; Noosorn, Narongsak (Journal of Medical and Public Health Region 4, 2023)
This descriptive research aimed to study the level of intention to stop substance abuse and predictors of intention to stop using substances among users after receiving addiction treatment in Phetchabun province. The sample consisted of 128 people. The reliability value of the whole questionnaire was 0.951 and the reliability values of each part of the questionnaire were between 0.720 - 0.963. The data were analyzed by multiple linear regression. The results of the study showed that the majority of the sample (84.40%) had the level of intention to stop substance abuse at the highest level. Significant predictors of intention to stop substance abuse were marital status (divorced or separated or widowed), normative beliefs, perceived behavioral control, and attitudes toward behavior. These factors predict 36.20 % of the variation of intention to stop substance abuse among users. Knowledge gained from this study suggests that the related organizations should study and develop a treatment model for substance abuse users that promotes positive attitudes toward behavior and perceived behavioral control. Norm’s participation should be included in the treatment process.